2023
DOI: 10.5304/jafscd.2023.122.021
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of food insecurity among LGBTQIA+ college students in North Texas: Meaning, experiences, and recommendations for inclusive solutions

Abstract: This ethnographic research explores the meaning and experiences of food insecurity among LGBTQIA+ college students to understand how identity might play a role in those experiences. We offer research-informed recommendations that stu­dent-serving programs could implement to increase accessibility and inclusivity for LGBTQIA+ students to reduce food insecurity. The study was conducted at a large, public, Tier 1 research univer­sity in North Texas. We used purposive sampling and recruited participants through em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Consistent with existing literature, our findings indicate stressors related to being part of a sexual and gender minority group have significant impacts on health and quality of life, in addition to the stressors already faced by college and university students (see for example, Frost et al, 2022;Haas & Lannutti, 2021;Henry et al, 2023;Laska et al, 2021). To buffer the negative effects of these stressors, many LGBTQIA2S+ individuals manage the visibility of their sexual orientations and/or gender identities by deciding whether to out themselves through subtle or overt expressions of sexual orientation or gender identity (Frost et al, 2022;Haas & Lannutti, 2021;Henry et al, 2023;James et al, 2016;Vale & Bisconti, 2021). Some participants in this research spoke about their ability to pass as cisgender and/or heterosexual.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with existing literature, our findings indicate stressors related to being part of a sexual and gender minority group have significant impacts on health and quality of life, in addition to the stressors already faced by college and university students (see for example, Frost et al, 2022;Haas & Lannutti, 2021;Henry et al, 2023;Laska et al, 2021). To buffer the negative effects of these stressors, many LGBTQIA2S+ individuals manage the visibility of their sexual orientations and/or gender identities by deciding whether to out themselves through subtle or overt expressions of sexual orientation or gender identity (Frost et al, 2022;Haas & Lannutti, 2021;Henry et al, 2023;James et al, 2016;Vale & Bisconti, 2021). Some participants in this research spoke about their ability to pass as cisgender and/or heterosexual.…”
Section: Discussionsupporting
confidence: 90%
“…The Hope Center found that students who identify as LGBTQ were more likely to experience basic needs insecurity and reported that 65% of LGBTQ students experience some form of basic needs insecurity, such as food insecurity, housing insecurity, and/or homelessness (The Hope Center, 2021). There has, however, been a lack of in-depth research on food insecurity amongst LGBTQIA2S+ university students, although recent research has begun to explore this topic (Collier et al, 2021;Henry et al, 2023). A myriad of factors may contribute to this gap in research, such as research on specific population intersections being more complex to study and analyze in comparison to studies focused on single population factor or a lack of research funding.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous students are also at higher risk (Alexis et al, 2020;Fausto, 2022;Reeder et al, 2020). LGBTIA+ students also experience food insecurity at higher rates than their heterosexual or cisgender peers, and they more often lack family support to mitigate their financial troubles (Henry et al, 2023;Willis, 2019). Another complicating factor is that college students underutilize Supplemental Nutrition Assistance Program (SNAP) benefits, at least in part because there are specific criteria for students that may make them unaware of their eligibility.…”
Section: Literature Reviewmentioning
confidence: 99%